Accelerated procedure for the enumeration and identification of food-borne Staphylococcus aureus. - Lachica, R V (1980)
A procedure was developed for accelerating to 29 h the enumeration and identification of both healthy and stressed cells of Staphylococcus aureus in foods. Baird-Parker agar medium was incubated for 24 h; S. aureus was identified within 5 additional h by using a simplified thermonuclease test.